Kandungan Zat Gizi Daun Kelor (Moringa Oleifera) Berdasarkan Metode Pengeringan - Zaki Irwan (Politeknik Kesehatan Kemenkes Mamuju, 2020)
Moringa leaf (moringa oleivera) is a multi-nutrient plant, especially Fe, As. Folat, Ca, phosphorus, but not yet used maximally in West Sulawesi, most of it is only used as a barrier to the yard of the house or garden. The purpose of this study was to determine differences in nutrient content (Protein, Ca, Fe, Posfor and Zn) in moringa leaf flour based on different drying methods. The research sample is Moringa leaves taken in 3 groups namely Moringa leaves based on the age of the leaves (shoots, young leaves, old leaves), each leaf group is divided into three based on the drying method, namely blanching, withering (aerated), and drying by drying. The research method uses true experiment, analysis of nutrient content by laboratory tests, protein content in moringa leaves is analyzed by the kjeldahl method, Fe, Ca, and Zn content is analyzed by atomic absorption spectrophotometer (AAS) method, phosphorus content is determined by UV-VIS spectrophotometer method. The tools used are oven blowers, containers (trays), kitchen tissue, rh meters, analytical scales, baskets, newspapers, gas stoves, basins, and pans. Hypothesis testing uses Two Way Anova to see differences in the nutritional content of Moringa leaves based on different drying methods. The results showed that the content of Protein (28.66), Zn (2.32) and Posfor (715.32), which is highest in drying by blancing method with p-value > 0.05. The content of Fe (11.41), and Ca (1014.81), the highest in moringa leaf flour with a drying method that is only aerated with p-value < 0.05. There is no difference in the content of Protein, Ca and Phosphorus and there are differences in the content of Fe and Zn based on the type of drying method. Prevention and prevention of stunting is recommended to use old moringa leaf flour with the method of drying withering to be used on PMT Toddler and Pregnant Women.